Two Suns? The Algorithmic State: History and Theory - Cleave, Peter (Te Kaharoa, 2021)
What follows is a history of cultural blindness. We might need to consider our historiography, the culture we find in the past, if you like, and the need to now reconstitute and re-frame that sense of history making the development of robotics and machine learning more central. Over in a usually forgotten corner there is a history of machines that may throw light on where we find ourselves today and in this section there is a consideration of that history, a story about robotics and theorists in this area unheard and unseen in many respects.